2013
DOI: 10.1088/0953-2048/26/7/075013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing superconducting properties of MgB2pellets by addition of amorphous magnetic Ni–Co–B nanoparticles

Abstract: Amorphous magnetic Ni-Co-B nanoparticles with an average size of 5 nm were added to precursor powders of MgB2 superconductor. The preparation procedure for MgB2 pellets was optimized for obtaining the best critical current density ( Jc) at elevated magnetic fields. Addition of Ni-Co-B decreases the Jc for heat treatment of precursor powders at 650 ° C. Heat treatments at 770 ° C and higher improve Jc at 20 and 5 K. This improvement occurs at both temperatures through the increase of the effective connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…10) show similarity with previous research on samples doped with Ni-Co-B nanoparticles 28,29,30 . All three observed curves have standard peaks associated with the melting of magnesium at 650ºC and the formation of MgB 2 at 750ºC.…”
Section: Mgb 2 Characterizationsupporting
confidence: 89%
“…10) show similarity with previous research on samples doped with Ni-Co-B nanoparticles 28,29,30 . All three observed curves have standard peaks associated with the melting of magnesium at 650ºC and the formation of MgB 2 at 750ºC.…”
Section: Mgb 2 Characterizationsupporting
confidence: 89%
“…It has been reported that the substitution of most doping elements on the Mg or B site lead to the suppression of Tc, [19] while the element and compound addition results in improvement of Jc, as mentioned earlier. Although there are some independent studies present, investigating the MgB2 samples with the performed addition of NiCoB nanoparticles, [20][21][22] they are mostly dealing with the effect of the addition of the nanoparticles on superconducting properties of MgB2. The microstructural analysis is mainly focused on the resulting MgB2 sample (formed after the addition of the nanoparticles to Mg and B precursor powders and sintering at various temperatures), [20] with relatively poor characterization of the identified constituent phases.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some independent studies present, investigating the MgB2 samples with the performed addition of NiCoB nanoparticles, [20][21][22] they are mostly dealing with the effect of the addition of the nanoparticles on superconducting properties of MgB2. The microstructural analysis is mainly focused on the resulting MgB2 sample (formed after the addition of the nanoparticles to Mg and B precursor powders and sintering at various temperatures), [20] with relatively poor characterization of the identified constituent phases. The characterization usually ends with quantitative analysis of the sample via Rietveld refinement (in form of obtained mass fractions of MgB2, MgO, and possible Mg if it is present).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations